Recursos de Humanidades Digitales para el estudio del teatro (traducido): Bases de datos, corpus y herramientas desarrollados en TRALIMA/ITZULIK - Andaluz Pinedo, Olaia; Sanjurjo-González, Hugo; Merino-Álvarez, Raquel (Talía. Revista de estudios teatrales, 2021)
Theatre research framed within Digital Humanities depends to a great extent on the availability of objects of study in digital format, as well as software that allows the application of different analysis techniques. In the TRALIMA/ITZULIK research group, databases, corpora and corpus processing tools have been developed. The creation of these materials and tools seeks to provide access to relevant contextual and textual data for research on translated theatre in Spain, an area that has usually received less attention than original theatre, despite its wide presence on stages. However, far from being restricted to the study of translated theatre, the databases and corpora include references to several agents of the Spanish theatre system that may be of use in different disciplines. In addition, the tools are adjusted to the specific structure of theatre texts to build and analyse monolingual, comparable and parallel corpora. The purpose of this article is to present the databases, corpora and tools developed by members of TRALIMA/ITZULIK for the study of (translated) theatre. By doing so, we aim to contribute to the spread of Digital Humanities resources available to researchers interested in the study of theatre from the variety of perspectives that characterises this multidisciplinary field.
Keywords: translated theatre; Digital Humanities; databases; corpora; corpus-based tools